2022
DOI: 10.31235/osf.io/bu9tx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infodemic Emergency in Italy: A Longitudinal Analysis of the Web Interest in Sources of Dis-Misinformation, Epidemiologically Dangerous Behaviors, and Vaccine Hesitancy During COVID-19

Abstract: Infodemic Emergency in Italy: A Longitudinal Analysis of the Web Interest in Sources of Dis-Misinformation, Epidemiologically Dangerous Behaviors, and Vaccine Hesitancy During COVID-19This paper investigates the web interest of Italian users in sources of COVID-19 dis-misinformation and assumption of behaviors in contrast to the anti-pandemic vaccination regulations. Infodemic keywords have been mined and verified thanks to the fact-checking websites "Bufale.net" and "Butac.it" and then searched on Google Tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In sum, evidence-based information about testing benefits and testing performance may contribute to both the individual (informed testing decisions and informed acceptance of granting) and the societal perspective (population-wide highly frequent testing intentions) on the large-scale implementation of rapid testing in times of a pandemic. Our indirect assessment of acquaintances' expected behaviors to cope with test-based granting suggests that between 10 to 30% of people potentially would cheat or prepare cheating to pretend a negative status, which is in line with actual web queries (Rovetta, 2022) and Darkweb markets (Georgoulias et al, 2022). At the same time, responses regarding compensation behavior indicate that up to 50% of people would have avoided untested people or places where they meet.…”
Section: Discussionsupporting
confidence: 53%
“…In sum, evidence-based information about testing benefits and testing performance may contribute to both the individual (informed testing decisions and informed acceptance of granting) and the societal perspective (population-wide highly frequent testing intentions) on the large-scale implementation of rapid testing in times of a pandemic. Our indirect assessment of acquaintances' expected behaviors to cope with test-based granting suggests that between 10 to 30% of people potentially would cheat or prepare cheating to pretend a negative status, which is in line with actual web queries (Rovetta, 2022) and Darkweb markets (Georgoulias et al, 2022). At the same time, responses regarding compensation behavior indicate that up to 50% of people would have avoided untested people or places where they meet.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, the population has already fronted pandemic fatigue resulting from two emotionally challenging years. In this regard, in Italy -one of the countries most affected by COVID-19 -there has been an alarming increase in the nonadherence to anti-contagion measures, even going so far as to buy or make counterfeit green passes [3].…”
mentioning
confidence: 99%
“…Users frequently search for conflict news, which can easily lead to fake news reading. The accredited anti-hoax website "Butac.it" -known for having been adopted in various infodemiological investigations and for collaborating with the Italian National Federation of Orders of Physicians and Dentists [3] -reported that the same sources of COVID-19 disinformation are now active about the conflict [5]. For all these reasons, we strongly suggest that government authorities implement adequate information strategies and use Google Trends to quickly monitor citizens' war-related web searches and topics of growing hype in order to intervene promptly and in a targeted manner.…”
mentioning
confidence: 99%